qanda-logo
apple logogoogle play logo

Calculator search results

Formula
Solve the equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
Graph
$y = 3 ^ { x }$
$y = 6$
$y$Intercept
$\left ( 0 , 1 \right )$
Asymptote
$y = 0$
$3 ^{ x } = 6$
$x = 1 + \log _{ 3 } { \left( 2 \right) }$
Solve the equation
$\color{#FF6800}{ 3 } ^ { \color{#FF6800}{ x } } = \color{#FF6800}{ 6 }$
$ $ Solve an exponential equation (inequality) by taking the logarithm on both sides $ $
$\color{#FF6800}{ x } = \log _{ \color{#FF6800}{ 3 } } { \left( \color{#FF6800}{ 6 } \right) }$
$x = \log _{ 3 } { \left( \color{#FF6800}{ 6 } \right) }$
$ $ Factor the antilogarithm with the expression in which $ 3 $ , that is the base, is included $ $
$x = \log _{ 3 } { \left( \color{#FF6800}{ 3 } \right) } + \log _{ 3 } { \left( \color{#FF6800}{ 2 } \right) }$
$x = \log _{ \color{#FF6800}{ 3 } } { \left( \color{#FF6800}{ 3 } \right) } + \log _{ 3 } { \left( 2 \right) }$
$ $ The logarithm is equal to 1 if a base is same as an antilogarithm $ $
$x = \color{#FF6800}{ 1 } + \log _{ 3 } { \left( 2 \right) }$
$ $ 그래프 보기 $ $
Graph
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple logogoogle play logo